2014
DOI: 10.1186/1756-0500-7-594
|View full text |Cite
|
Sign up to set email alerts
|

Impaired quality of life in patients with systemic sclerosis compared to the general population and chronic dermatoses

Abstract: BackgroundSystemic sclerosis (SSc) is a rare and potentially life threatening autoimmune disorder. The burden of disease compared to other dermatoses is unknown. The purpose of this study was to assess both the quality of life in patients with SSc and the variables that are associated with poor quality of life. Forty-one patients with systemic sclerosis (29 limited, 2 diffuse, 10 undifferentiated forms) were assessed with respect to their health status and compared to published data for the normal population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
(61 reference statements)
2
18
0
5
Order By: Relevance
“…Embora saiba-se que a QV de indivíduos com ES seja prejudicada, especialmente em idosos [13][14][15] , e que a capacidade de gerar força tende a diminuir com o avanço da idade 19 , até o presente momento não haviam registros sobre a correlação da FPP e QV em idosos com ES. Este estudo demonstrou que com o aumento da FPP houve também melhora dos escores dos domínios da QV em um idoso longevo com ES.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora saiba-se que a QV de indivíduos com ES seja prejudicada, especialmente em idosos [13][14][15] , e que a capacidade de gerar força tende a diminuir com o avanço da idade 19 , até o presente momento não haviam registros sobre a correlação da FPP e QV em idosos com ES. Este estudo demonstrou que com o aumento da FPP houve também melhora dos escores dos domínios da QV em um idoso longevo com ES.…”
Section: Discussionunclassified
“…Estudos atuais referenciam que a QV de indivíduos com ES possa ser impactada negativamente em aspectos físicos e cognitivos se comparado com indivíduos sem a patologia, inclusive nos idosos [13][14][15] . A funcionalidade pode ser mantida através da fisioterapia, sobretudo a cinesioterapia, a qual tem papel fundamental no tratamento da ES por prevenir os agravos osteomioarticulares, como os quadros de dor, as contraturas e a diminuição da amplitude do movimento e da força muscular, além de proporcionar a melhora e a manutenção da QV destes acometidos 6,15 .…”
Section: Introductionunclassified
“…In chronic situations, pain goes beyond the physiological period of tissue healing, causing physical and cognitive incapacity or impairing patients' wellbeing and QL 15 . So, QL of SS patients may be impaired as compared to healthy individuals 16 , because it is inversely correlated to pain 9 . This is suggested by our study, because results have shown that when QL scores improved, pain scores decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Salt and pepper appearance was the cutaneous finding that had association with high dermatology life quality index scores [16]. In SSc patients skin remission cannot be achieved like in others dermatoses (psoriasis, atopic dermatitis, pemphigus, or SLE) [10] and so the social factors and disease coping may contribute to a better mental health [84][85][86].…”
Section: Skin Deformities and Disfigurementmentioning
confidence: 99%